Analysis of the risk of death and its associated risk factors in Chinese patients with young-onset type 2 diabetes - Wu, Dan; Yu, Yang; Zheng, Haoran; Xiang, Ling; Wang, Xiaoqing; Zhang, Yong; Sun, Zhongming; Miao, Dandan; Zhou, Jinyi; Pan, Enchun; Hu, Wen (Frontiers in Endocrinology, 2024)
ObjectivesTo examine the association between the age at onset of diabetes and the risk of all-cause mortality in a population of individuals diagnosed with type 2 diabetes mellitus (T2DM) and to identify risk factors associated with all-cause mortality in young-onset T2DM (YOD) patients in China.MethodsThis study utilized a cohort of 9759 patients who were diagnosed with T2DM and who were registered and enrolled in the National Basic Public Health Service Management Program in Qinghe District (now Qingjiangpu District) and Huai’an District, Huai’an City, Jiangsu Province, China. The patients were observed from November 2013 to July 2014, and all-cause mortality data were obtained by comprehensive matching with the Huai’an City Resident Mortality Database as of December 31, 2019. A Cox proportional hazards model was used to compute the hazard ratios (HRs) and their corresponding 95% confidence intervals (95% CIs) for all-cause mortality risk during the follow-up period among patients with varying disease onset ages. Additionally, subgroup analyses were conducted based on sex, age, lifestyle factors, and baseline clinical parameters.ResultsA total of 7572 patients with T2DM, including 2874 men and 4698 women aged 57.9 ± 8.0 years, were ultimately included in the study. 1) At baseline, a greater proportion of YOD patients were engaged in high-intensity activities, had a longer sleep duration, had a longer duration of T2DM, had a family history of T2DM, had microvascular complications (kidney disease, retinopathy, neuropathy, diabetic foot, etc.), and received glucose-lowering treatment. Moreover, patients in the YOD group also had significantly greater baseline HbA1c, FBG, and estimated glomerular filtration rate (eGFR) than did those in the onset at 41-60 years (MD) group and the onset at 61-75 years (SD) group. 2) During the six-year follow-up period, a total of 1057 deaths were documented. After adjusting for confounding factors and utilizing SD as the reference group, the HRs for deaths occurring in the YOD and MD groups were 1.383 (95% CI: 0.717-2.667) and 1.006 (95% CI: 0.763-1.326), respectively. Moreover, the risk of death in the YOD group remained highest in the sensitivity analysis that excluded patients with coronary heart disease at baseline, stroke patients, and patients who died within the first three years of follow-up. 3) Sleep duration was identified as an independent risk factor for mortality in the YOD group, with a notable increase in the risk of all-cause mortality when sleep duration exceeded 9 hours per day.ConclusionThe risk of all-cause mortality in YOD patients was 1.38 times greater than that in MD and SD patients, and the longer the sleep duration was, the greater the risk of death, especially when sleep duration exceeded 9 hours per day.